Parental Time of Returning Home From Work and Child Mental Health Among First-Year Primary School Students in Japan: Result From A-CHILD Study - Kizuki, Masashi; Ochi, Manami; Isumi, Aya; Kato, Tsuguhiko; Fujiwara, Takeo (Frontiers in Pediatrics, 2018)
Introduction: Child mental health is known to be influenced by parental work hours. Although literature suggests that parent-child interaction mediates the association, few studies have directly measured the parental time of returning home from work. We analyzed data from a school-based survey to examine the association between parental time of returning home from work and child mental health. Methods: We used a sample of 2987 first-year primary school students derived from the Adachi Child Health Impact of Living Difficulty (A-CHILD) study that examined the impact of family environment and lifestyle on child health in Adachi City, Tokyo, Japan. We analyzed the associations between reported parental time of returning home and the continuous Strengths and Difficulties Questionnaire (SDQ) scores using multivariable regression modeling. Results: Children whose parents both returned home late (later than 6pm for the mother and later than 8pm for the father), or at irregular times, had higher scores in total difficulties (β = 1.20, 95% CI: 0.55 to 1.85), the ‘conduct problems’ subscale (β = 0.37, 95% CI: 0.13 to 0.60), and the hyperactivity/inattention subscale (β = 0.53, 95% CI: 0.24 to 0.82) compared with children whose parents both returned home earlier. Mediation analyses indicated that the percentage of the total association between parental time of returning home and the SDQ scores, which was mediated by parent-child interaction, was 20% (95% CI: 10 to 46) for total difficulties, 17% (95% CI: 7 to 49) for conduct problems, and 23% (95% CI: 11 to 52) for hyperactivity/inattention. Conclusions: Late or irregular returning home times for both parents had an adverse effect on child mental health, and the relationship was partly mediated by reduced frequency of parent-child interaction.